Singlet‐Oxygen Generation by Peroxidases and Peroxygenases for Chemoenzymatic Synthesis - Ingenbosch, Kim N.; Quint, Stephan; Dyllick‐Brenzinger, Melanie; Wunschik, Dennis S.; Kiebist, Jan; Süss, Philipp; Liebelt, Ute; Zuhse, Ralf; Menyes, Ulf; Scheibner, Katrin; Mayer, Christian; Opwis, Klaus; et al. (Chembiochem : a European journal of chemical biology, 2021)
Singlet oxygen is a reactive oxygen species undesired in living cells but a rare and valuable reagent in chemical synthesis. We present a fluorescence spectroscopic analysis of the singlet‐oxygen formation activity of commercial peroxidases and novel peroxygenases. Singlet‐oxygen sensor green (SOSG) is used as fluorogenic singlet oxygen trap. Establishing a kinetic model for the reaction cascade to the fluorescent SOSG endoperoxide permits a kinetic analysis of enzymatic singlet‐oxygen formation. All peroxidases and peroxygenases show singlet‐oxygen formation. No singlet oxygen activity could be found for any catalase under investigation. Substrate inhibition is observed for all reactive enzymes. The commercial dye‐decolorizing peroxidase industrially used for dairy bleaching shows the highest singlet‐oxygen activity and the lowest inhibition. This enzyme was immobilized on a textile carrier and successfully applied for a chemical synthesis. Here, ascaridole was synthesized via enzymatically produced singlet oxygen. H2O2 to 1O2 to… The formation of singlet oxygen from hydrogen peroxide by heme peroxidases and peroxygenases, but not catalases, is shown by fluorescence spectroscopy. The most active peroxidase, based on kinetic analysis using the fluorescent trap singlet‐oxygen sensor green, was applied in a chemo‐enzymatic synthesis of ascaridole.